Safe Zones for Spinopelvic Screws in Patients With Lumbosacral Transitional Vertebra. Issue 4 (May 2023) - Becker, Luis; Schömig, Friederike; Haffer, Henryk; Ziegeler, Katharina; Diekhoff, Torsten; Pumberger, Matthias
Study Design: Retrospective matched-pair analysis. Objectives: Lumbosacral transitional vertebrae (LSTV) have a reported prevalence of 4-36% in the population. The safe zones for screw placement for spinopelvic fusion in adult spinal deformity surgery for patients with LSTV have not been described in the literature. Our study aimed to assess the safety of S1-pedicle screw (S1PS), S2-alar screw (S2AS), S2-alar-iliac screw (S2AIS), and iliac screw (IS) placement in patients with LSTV. Methods: Out of the 819 examined patients, 49 patients with LSTV were included in our retrospective analysis with a matched pair control group. We used the 3-dimensional planning tool mediCAD for screw placement of S1PS, S2AS, S2AIS, IS with different angles, length and diameters. Results: We evaluated a total of 10 192 screw trajectories. No serious complications occurred due to the trajectories used for S1PS. LSTV increased the risk of vessel injury for S2AS trajectories ( P = .001) but not for S2AIS ( P = .526). Besides the presence of an LSTV, the screw trajectory had a major influence on the frequency of serious complications. Conclusions: Sacral anchoring of long spinal constructions using S1PS, S2AS, S2AIS and IS is also possible in the presence of LSTV. For S2AS the trajectory with 30° lateral and caudal angulation of 10° showed the least vascular injuries and the least sacro-iliac-joint violations in patients with LSTV. S2AIS trajectories with 40° lateral and 0° sagittal angulation reduced the risk of serious complications in our patients collective with LSTV.